2018
DOI: 10.1589/jpts.30.1381
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of muscle activity at different gait phases for improving walking performance in chronic stroke patients with hemiparesis

Abstract: [Purpose] The aim of this study was to clarify the optimal timing for increasing muscle activity in the paralyzed lower limb of stroke survivors by evaluating the relationship between gait muscle activity patterns and gait parameters. [Participants and Methods] Electromyography of the tibialis anterior, soleus, rectus femoris, and biceps femoris on the paralyzed side and spatiotemporal gait parameters were evaluated in 40 chronic post-stroke patients as they walked at a comfortable speed. The normalized averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The knee muscle contraction has eccentric contractions and concentric contractions in certain gait phases (Kerrigan dan Edelstein, 2001). There is not clear what contributes to the decreased ability to walk after a stroke (Flansbjer, 2006;Fujita et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The knee muscle contraction has eccentric contractions and concentric contractions in certain gait phases (Kerrigan dan Edelstein, 2001). There is not clear what contributes to the decreased ability to walk after a stroke (Flansbjer, 2006;Fujita et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any nonlinearity would result in decreased momentum and slower load transfer during gait, leading to a disruption in forward progression. ABI patients with hemiplegia often present with reduced hip flexion, dorsiflexion, and plantarflexion during the initial loading phase due to muscle paresis [11,31]. This results in the tibia not rolling forward over the calcanium, which is observed as non-linearity, to complete the transfer of the body weight from the contralateral limb [11].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Kolaghassi et al [23], focussed on continuous variable prediction only, identified a similar bias in the scientific literature where 72% of studies predicted angle joints and only 28% predicted torque and moment joints. The majority of studies employing EMG only to predict movement measured lower-limb muscle groups of RF and VL, two muscles that are highly active during gait [74,75]. Both muscles extend the knee joint.…”
Section: Emgmentioning
confidence: 99%